Evaluation of Information System Governance Using the COBIT 2019 Framework - Dian Novianti; Sunardi Sunardi; Imam Riadi (bit-Tech, 2026)
Effective information system governance is a crucial factor in supporting the performance of higher education institutions, yet many universities still face challenges in implementing structured and standardized information technology governance. Evaluation of governance capability levels is necessary to identify weaknesses and determine appropriate improvement priorities. This study aims to evaluate the level of information system governance capability at the Faculty of Engineering using the COBIT 2019 framework and identify gaps between actual conditions and expected capability levels. This study uses a case study approach, adopting the APO, BAI, DSS, and MEA domains from COBIT 2019. Data collection was conducted through questionnaires, interviews, observations, and documentation, and the data were analyzed using the COBIT 2019 capability model and gap analysis. The results show that all information system governance domains are below the Level 3 (Established Process) target, with the DSS domain having the highest capability level and the MEA domain showing the lowest level, with the largest gap. Most processes are still at Level 2 (Managed Process), indicating they have been running but not formally documented or standardized. In conclusion, the identified capability gaps, particularly in the MEA and BAI domains, highlight the need for strengthening formal monitoring mechanisms, process standardization, and structured system development practices to enhance governance effectiveness, support strategic decision-making, and ensure sustainable information system management within the Faculty of Engineering.